Pengaruh Gaya Kepemimpinan Terhadap Prestasi Kerja Dinas Pendidikan Dan Kebudayaan Kabupaten Batang Hari - Budi Darma (CITRA EKONOMI, 2021)
This study entitled The Effect of Leadership Style in Efforts to Improve Job Performance in the Education and Culture Office of Batang Hari Regency. As one of the government agencies, employees are required to work well. In work, of course, will lead to an achievement called work performance. In analyzing the data, the analysis tool used is the t test, and the coefficient of determination and simple linear regression. In the t test, it will be concluded that the variable of leadership style has an effect or not partially (individually) on work performance. In the Coefficient of Determination, the magnitude of the effect that occurs will be calculated as a percentage. To determine the effect of leadership style on work performance at the Batang Hari Regency Education and Culture Office, it can be seen from the t test and the coefficient of determination. In the t test, it is known that the leadership style has a partial effect on work performance. Then, based on the coefficient of determination, leadership style affects work performance at the Batang Hari Education and Culture Office by 27.8%.